2010
DOI: 10.1007/s00259-009-1355-y
|View full text |Cite
|
Sign up to set email alerts
|

PET/CT imaging of osteoblastic bone metastases with 68Ga-bisphosphonates: first human study

Abstract: Bisphosphonates are well established ligands for 99m Tc for planar and SPECT/CT imaging of osteoblastic metastases. A novel DOTA-based bisphosphonate, (4-{[bis-(phosphonomethyl)) carbamoyl]methyl}-7,10-bis(carboxymethyl)-1,4,7,10-tetraazacyclododec-1-yl)acetic acid (BPAMD) [1,2] The advantages of this new bone imaging PET tracer are the very high target to soft tissue ratios and fast clearance, its ease of use and the generator-based availability of 68 Ga which becomes especially important in these days of 99… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 3 publications
4
78
0
1
Order By: Relevance
“…However, they stated that the advantage of 68 Ga-EDTMP over [ 18 F]-fluoride was not apparent and that the future clinical prospect of 68 Ga-EDTMP remained speculative. Meanwhile, PET/CT imaging of bone metastases with a 68 Ga-DOTA complex-conjugated bisphosphonate (BPAMD) based on a strategy similar to our study has been reported [29]. 68 Ga-BPAMD showed high uptake in osteoblastic metastases.…”
Section: Discussionsupporting
confidence: 66%
“…However, they stated that the advantage of 68 Ga-EDTMP over [ 18 F]-fluoride was not apparent and that the future clinical prospect of 68 Ga-EDTMP remained speculative. Meanwhile, PET/CT imaging of bone metastases with a 68 Ga-DOTA complex-conjugated bisphosphonate (BPAMD) based on a strategy similar to our study has been reported [29]. 68 Ga-BPAMD showed high uptake in osteoblastic metastases.…”
Section: Discussionsupporting
confidence: 66%
“…Distinct values of the complex ligands (100-400 nmol) were added to the lutetium-containing vials. By varying pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and temperature (50-100°C), the effect of these parameters was investigated based on ITLC results. For radio thin layer chromatography, a 5 lL sample of the final fraction was spotted on a chromatography Whatman No.…”
Section: Preparation and Quality Control Of 177 Lu-bpamdmentioning
confidence: 99%
“…(4-{[(bis(phosphonomethyl))carbamoyl] methyl}-7,10-bis(carboxymethyl)-1,4,7,10-tetraazacyclododec-1-yl)acetic acid (BPAMD) (Fig. 1), as a new macrocyclic diphosphonate, in labeling with 68 Ga, in first human studies showed promising results such as very high target-tosoft-tissue ratios and ultrafast clearance [12]. It has been shown that the BPAMD complex, as a new generation of DOTA bisphosphonate, can solve the mentioned limitations of the first generation phosphonates either in diagnostic or in therapeutic applications [11].…”
Section: Introductionmentioning
confidence: 97%
“…Briefly, distinct values of the complex ligands were added to the 68 Ga-containing vials. By varying pH (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) and temperature (50-100°C), the effect of these parameters was investigated based on ITLC results. The optimal procedure for the preparation of 68 Ga-ECC complex with a high labeling yield was obtained.…”
Section: Preparation and Quality Control Of 68 Ga-eccmentioning
confidence: 99%
“…The efficacies of 68 Ga-based tracers are comparable to that of 18 F-based agents and have stimulated researchers to investigate the potential of 68 Ga-based PET imaging agents [4] and nowadays, numerous 68 Ga-based radiopharmaceuticals have been found useful in clinical studies [5][6][7].…”
mentioning
confidence: 99%